Abrupt climate change events from the past could help predict the ones ahead. (Research'eu results magazine)
Coping with climate change will already be difficult enough without worrying about Dansgaard-Oescheger (DO) events that could come on top of it. However, their possible occurrence cannot be dismissed : We need to know more about these events, how they impacted our planet in the past, and how they could continue to do so in the future. The world's most well-preserved ice cores could provide all this information while allowing for improved climate models.